Questões de identidade lingüístico-cultural e sua relação com a oralidade em LE (Inglês): percepções de aprendizes em nível intermediário - Paschoal, Luciane Cristina (2011)
When learning a foreign language, more specifically English, it is common that students report that speaking is the most difficult skill to be developed. This difficulty may be related to the lack of a critical view about identity and culture and, hence, students may not value their culture and language. Some students may consider the foreign language superior (RAJAGOPALAN, 2003) and, therefore, may not take risks during oral practice in classroom, which might influence the development of oral competence. It is possible to notice the need of a critical literacy on foreign language, whose objective is to empower students to reflect about their identity and analyze their learning process in a critical way. Based on critical applied linguistics (PENNYCOOK, 2006), this research has the objective to verify how critical literacy may help learners develop a critical view about their culture and language and to analyze if reflections about identity might help students in the development of their oral competence of English as a foreign language (EFL). To answer the following research questions What is the initial perception of students about their culture and about foreign culture? ; Does critical literacy foster awareness about their language and culture? ; and How can the process of (re)construction of identity influence the perception of orality in EFL? , a qualitative (ERICKSON, 1984) interpretativist research (HOLMES, 1992; MOITA LOPES, 1994) was carried out. Data was collected and recorded through individual interviews and focus groups during the first semester of 2010. Analyses were developed through data triangulation (VIANA, 2007) based on theories about identity (BHABHA, 2003; RAJAGOPALAN, 2003; HALL, 2006), EFL learning (ALMEIDA FILHO, 2002) and critical literacy (BARTON, 1994). The results show that critical literacy was important to empower students and to improve the development of oral competence.